Designing Future Policy Scenarios for Sustainable Urban Freight Transport: Lessons from the Jakarta Greater Area - Fathurrahman, Reza; Afra, Syifa Amania (Khazanah Sosial, 2025)
As the center of economic growth and the hub of industries and trade in Indonesia, the issue of goods transportation development in the Jakarta Greater Area deserves higher priority, amongst academics, private sector leaders, and policymakers. Currently, freight trucking is the most widely used mode of goods transportation within the Jakarta greater area (91.3 percent), exceeding the other two alternative modes: sea (7.6 percent) and railway (1.1 percent) transportation. However, the movement of goods transported along the corridor is very congested, not environmentally friendly, and has a relatively small efficiency value and economies of scale. On the other hand, the train mode offers several advantages over the truck mode, including a large transport capacity, relatively fast travel times, freedom from illegal levies, and more guaranteed goods safety. This article employs a mixed-methods approach that combines documentary and SWOT Analysis to explore the current and prospective status of freight railways in the Jakarta region as perceived by key multiple stakeholders, including national and provincial governments, the private sector, academia, and civil society organizations. The results reveal vertical and horizontal disharmony among the responsible government units at both the national and provincial levels regarding the future direction of Jakarta's freight transport. Interestingly, during the FGD, the rational trucking business owners did not show any reluctance toward railway development, as it turned out that a more integrated, intermodal transportation is a better option for all. Finally, the DKI Jakarta Provincial Government needs to prioritize its resources to address the existing weaknesses and challenges before expanding further with a broader and more ambitious strategy.